1980
DOI: 10.1159/000179128
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Thyroxine to Triiodothyronine and Reverse Triiodothyronine in Human Placenta and Fetal Membranes

Abstract: Conversion of thyroxine (T4) to 3,5,3’-triiodothyronine (T3) and reverse 3,3’,5’-triiodothyronine (rT3) was measured in vitro in human placenta and fetal membranes. T4 (5 µg/ml) was incubated in 0.15 mol/l phosphate buffer with tissue homogenates for 2 h at 37°C, and the T3 and rT3 generated were determined in ethanol extract using RIA methods. The placenta and chorion homogenates converted more T4 to T3 than to rT3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1983
1983
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The added T4 concentration in assay C, 1 nM, was much greater than that contributed by the T4 content of cells cultured in either type of serum: 125±25 pM from cells in normal calf serum and 26±6 pM from cells in THDCS, as monitored by tracer T4 added to parallel wells. 2 Thus, all three assays showed a near doubling of 5'-deiodination after 48 h deprivation ofthyroid hormone. The increase 2.…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…The added T4 concentration in assay C, 1 nM, was much greater than that contributed by the T4 content of cells cultured in either type of serum: 125±25 pM from cells in normal calf serum and 26±6 pM from cells in THDCS, as monitored by tracer T4 added to parallel wells. 2 Thus, all three assays showed a near doubling of 5'-deiodination after 48 h deprivation ofthyroid hormone. The increase 2.…”
Section: Methodsmentioning
confidence: 79%
“…The chorion-decidual membrane was then minced and submitted to digestion in HBSS with 2 Cells liberated between 30 and 90 min were passed through a 149-gm nylon mesh and collected. Cell viability, assessed by trypan blue exclusion, was 82-94%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also shown that T4 is converted to 3,3',5'-tri-iodothyronine (reverse T3) in the brain (Kaplan and Yaskoski 1980), liver (Cavaliers et al 1977), kidney (Yoshida et al 1982) and leucocytes (Woeber 1978). Recently, it has been reported that T4 is metabolized in the placenta (Banovac et al 1980; Roti et al 1981). In the present paper, we describe the T4 monodeiodination to reverse T3 in vitro in the human placental homogenate and subcellular fractions obtained from the placentas at normal delivery.…”
mentioning
confidence: 99%
“…The iodothyronine markers were detected at a wavelength of 254 nm and were used as reference points for 1251 radioactivity eluting from the column. Table I shows the retention times for ['25Iliodide and stable 3'-TI, 3,3'-T2, 3',5'-T2, 3,5-T2, T3, and T4. HPLC eluate fractions were collected every 0.6 min and counted in a gamma counter.…”
Section: Methodsmentioning
confidence: 99%